Mussel-inspired fabrication of functional materials and their environmental applications: Progress and prospects. (June 2017) - Zhang, Xiaoyong; Huang, Qiang; Deng, Fengjie; Huang, Hongye; Wan, Qing; Liu, Meiying; Wei, Yen
Graphical abstract: The recent development and advances of mussel-inspired chemistry for surface modification and related functional materials for environment applications were summarized in this review. Highlights: Surface modification of materials and surfaces through mussel-inspired chemistry. The mussel-inspired strategy is rather simple, effective and universality. These functional materials are promising for environmental applications. The mussel-inspired chemistry are also promising for fabrication of other functional materials. Abstract: Mussel-inspired chemistry has recently emerged as one of the most important and interest surface modification method owing to its gentle experiment conditions, high modification efficiency and universality. The mussel-inspired chemistry is mainly relied on the adhesion of dopamine toward various materials and surfaces. In recent years, great efforts have been devoted to understanding the adhesion mechanism of mussel and extending its applications in different fields. In this mini-review, we present the very recent development of mussel-inspired fabrication of functional materials for environmental applications. The surface modification strategies that based on mussel-inspired chemistry were outlined in the first part. The environmental applications (e.g. oil/water separation, environmental adsorption and catalysts) based on these functional materials are also highlighted in the following sections. Although many advances have been achieved, there still have a plenty of spaces for further development of mussel-inspired surface chemistry for functional materials and their environmental applications.